KOMUNIKASI INTERPERSONAL ISTRI YANG BELUM DIKARUNIA ANAK DI KELURAHAN SIAK HULU KAMPAR - Ermairel Salim (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
This research was conducted at Griya Kenari Village of Siak Hulu Kampar Riau. The purpose of this study was to find out how positive attitude in interpersonal communications of wives who have not yet gifted children in Siak Hulu Kampar. Benefits of this research is a contribution of science to STISIP Persada Bunda Pekanbaru and train the ability of writers in conducting research. Communication is a very fundamental need for a person in social life. Humans can not not communicate, because it is a creature that is dikodratkan to live communicate. Place of research conducted in Village Siak Hulu Kampar, precisely in Housing Griya Kenari Indah and Bhakti Karya. Research subject Wives who have not been blessed child / offspring.Waktu research is March to June 2017. This researcher uses purposive sampling. Informant of this study Wives who have not blessed children / offspring of 4 families and communities Griya Kenari Housing Indah and Bhakti Karya totaling 10 people. Based on the results of the research it can be concluded that good interpersonal communication will open the door of good communication with others and interpersonal Communication is less fun with others will cause things that are not good also for others.